The prevailing wage system toward the potential of trade unions in local situations - Supiyah, Ratna; Komariah, Kokom; Hubur, Aa; Chauhan, Rahul; Artha, Ruly (Linguistics and Culture Review, 2021)
Impatience with the prevailing wage system - due to its components that place too much emphasis on non-monetary rewards and too much emphasis on age and seniority - is evident among young workers. The Directors strongly felt that the growing pool of trained workers in the city did not fit into the current system of relations in the factory. These feelings are expressed both in training programs intended to instill traditional values ??and in prevailing recruitment procedures. There are no examples of other types of tension and anxiety-caused by lagging the current factory system from (to) the changes taking place. In society at large - rather than the role of women in Japanese companies. Perhaps more than any other interaction. The relationship between men and women in Japan is very different from what has developed in the West. Perhaps more than any other type of relationship, the changes caused and accelerated by the events of the last years have influenced the roles, attitudes and behavior of Japanese women. The resulting tensions were evident in factories and in the offices of large Japanese companies.